Comportamento de consumo ecologicamente consciente dos universitários do Instituto de Ciências Exatas e Tecnologia ICET/UFAM - Souza, Aline de Oliveira (Brasil, 2023)
This research aimed to analyze the CCEC of university students, through 5 factors, perceived consumption effectiveness, environmental concern, external motivators, green attitude and green consumption behavior. The applied methodology was an exploratory study, with a quali quantitative approach, using a questionnaire via Google Forms, containing questions to survey the profile, as well as using a Likert scale to measure the level of agreement with the proposed statements. The analyzed population were the graduates of the Federal University of Amazonas (UFAM), more specifically at the Institute of Exact Sciences and Technologies (ICET), located in the municipality of Itacoatiara, in the interior of the State of Amazonas. Data analysis was performed using basic statistics, using programs such as Excel and Power BI, the Average Ranking (RM) per factor was calculated. It was identified that the factors with the highest RM were environmental concern and perceived effectiveness of consumption, indicating that students are aware of environmental problems and their ability to participate in solutions, as well as the impact that their consumption behavior has on the environment. The factor with the lowest RM was external motivators, mainly due to the unavailability of green products. The study demonstrated that university students condition their ecological behavior to personal satisfaction, in a way that they present pro-environmental behavior, as long as they obtain personal advantages at the same time.